Qurrat al-ʿAyn, the Maiden of the Kaʿba: On the Themenophany Inspiring Ibn ʿArabī’s Tarjumān - Beneito, Pablo (Religions, 2021)
Qurrat al-ʿAyn is the name of the enigmatic Maiden who appeared alongside Ibn ʿArabī when he was inspired to recite the four verses that open The Interpreter of Desires, as he was wandering around the Kaʿba. In this article, through the analysis of the passage in which she is mentioned, the identity of the Maiden is explored from various perspectives typical of the author’s theo-anthropo-cosmovision, characterised by his concept of theophany (tajallī) or divine self-revelation, resorting especially to both the analysis of the lexical inter-reference in the roots of the Arabic terms used by Ibn ʿArabī in his Tarjumān al-ashwāq, as well as the study of the symbolism characteristic of the Arabic alphanumeric system. Furthermore, the article proposes that the kaleidoscopic structure of this collection of odes, studied here for the first time, is the result of a themenophany of the Kaʿba: the Tarjumān has been “inspired” by/on the Kaʿba itself, so that in a sense it is a bibliophany of the so-called House of God, to whose geometry—four corners, six faces, seven ritual turns, eight vertices—its structural conception corresponds. The symbolism of Arabic geomancy in relation to the structure of the Tarjumān is also considered.